Writing and publication workshop - UiTM, Faculty of Law (Faculty of Law, 2019)
On 7-8 March 2019, a Writing and Publication Workshop was held at the Faculty of Law, the first of the many initiatives and programmes which will be conducted throughout the academic year. The programme was kickstarted with a talk by an experience journal reviewer, Prof. Dr. Faridah Hassan, a resident reviewer for Institute of Quality and Knowledge Advancement (InQKA), UiTM. Fifteen staff joined the session which also involved sharing their own experiences publishing in top journals. During the afternoon slot, our beloved Assoc. Prof. Dr. Zaiton Hamin gave a talk on how to write and publish in journals and shared her own experience in publishing in Q1-Q4 ranked journals. The next day, our Ranking Champion Coordinator, Dr. Nur Ezan Rahmat conducted a hands on workshop on how to find journals listed on SCOPUS and briefed the participants on how to submit articles in the new e-rts system which allows resident reviewers to review and comment on the articles submitted. The e-rts is a new initiative by InQKA to encourage and help academics in UiTM to write and send their articles to SCOPUS ranked journals.